Coixol ameliorates dopaminergic neurodegeneration by inhibiting neuroinflammation and protecting mitochondrial function - Yang, Shuo; Han, Jiaxi; Xue, Miao; Zhang, Yiming; Yan, Aohan; Gao, Xiyu; He, Jiangmei; Sun, Xiaojia; Fu, Shoupeng; Liu, Dianfeng; Huang, Bingxu (Frontiers in Pharmacology, 2025)
Extensive research has revealed that neuroinflammation plays an important role in Parkinson’s disease (PD). Coixol, extracted from Coix lacryma-jobi L., exhibits anti-inflammatory and antioxidant effects in various diseases. However, the effect of coixol on PD remains unclear. The aim of this study is to investigate the effects of coixol in a 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP)-induced PD mouse model. Our results show that coixol improves the motor dysfunction and neuronal damage in PD mice by inhibiting neuroinflammation and maintaining mitochondrial function. Moreover, coixol suppressed the overactivation of the nuclear transcription factor κB (NF-κB) and the mitogen-activated protein kinase (MAPK) signaling pathways and regulated the NLR family pyrin structural domain 3 (NLRP3)/cysteinyl aspartate-specific proteinase-1 (Caspase1)/interleukin-1β (IL-1β) signaling pathway to inhibit neuroinflammation in PD mice. The results show that coixol mitigated reactive oxygen species (ROS)-induced mitochondrial damage, thereby inhibiting the overactivation of the NLRP3 inflammasome. Taken together, we found that coixol alleviates dopaminergic neurodegeneration in PD mice by inhibiting the activation of NF-κB and MAPK signaling pathways to suppress neuroinflammation and protect mitochondrial function from ROS production to regulate NLRP3 inflammasome activation.